Comparison of poloxamer- and chitosan-based thermally sensitive gels for the treatment of vaginal mucositis. (March 2014) - Rossi, Silvia; Ferrari, Franca; Bonferoni, Maria Cristina; Sandri, Giuseppina; Faccendini, Angela; Puccio, Antonella; Caramella, Carla
Abstract Context: The local treatment of vaginal mucositis requires an intimate and prolonged contact of anti-infective drugs with the mucosa. This can be achieved by means of mucoadhesive and thermally sensitive vehicles, capable of gelifying at the physiological temperature. Objective: The aim of the present work was to compare the potentiality of poloxamer 407 (PLX)/chitosan lactate (CS-L) and CS-L/glycerophosphate (GP) mixtures as mucoadhesive thermally sensitive vehicles for the treatment of vaginal mucositis. Materials and methods: PLX/CS-L and CS-L/GP mixtures were characterized for gelation and mucoadhesion properties as well as for bioactive (antimicrobial and wound healing) properties. Finally, the mixtures were loaded with amoxicillin trihydrate as model drug and characterized for drug release and washability properties. Results and discussion: The addition of CS-L to PLX causes an increase in PLX gelation temperature from 30 °C to the physiological temperature. The dilution with simulated vaginal fluid causes an increase in gelation time of PLX/CS-L mixture, while no variation of such parameter is observed for CS-L/GP mixture which is nevertheless characterized by poorer elastic properties. The stronger mucoadhesion properties of CS-L/GP mixture counterbalance the poorer elasticity of the gel and are responsible for a longer drug contact with the biological substrate. CS-L/GP mixture is moreover characterized by better bioactive properties than PLX-based mixture. Conclusion: CS-L/GP mixture represents a promising thermally sensitive vehicle.